1991
DOI: 10.1161/01.str.22.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent changes in cerebral choline and acetylcholine induced by transient global ischemia in rats.

Abstract: We occluded the carotid and vertebral arteries of 12 rats for 15 minutes to measure the brain concentrations of choline and acetylcholine and cerebral blood flow at the end of the ischemic period or 15,30, or 150 minutes after circulation was reestablished. The animals were sacrificed with microwave radiation focused to the head immediately after a brief infusion of [ 14 C]iodoantipyrine with rapid sampling of arterial blood. Brain tissue samples were extracted with ether to separate the tracer, which was subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 18 publications
(9 reference statements)
0
24
0
Order By: Relevance
“…This could be especially true in cases of trauma or stroke, when choline concentrations in the brain increase to as high as 100 M (Jope and Gu, 1991;Scremin and Jenden, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…This could be especially true in cases of trauma or stroke, when choline concentrations in the brain increase to as high as 100 M (Jope and Gu, 1991;Scremin and Jenden, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…20,21) Moreover, many studies have demonstrated that ischemia causes a reduction of memory and judgment that is associated with the cholinergic dysfunction in affected brain areas 22) and that ischemic insults decreases in ACh level in the affected regions of the brain. [23][24][25] Thus, in animals subjected to transient ischemia, an impairment of spatial cognitive performance in a water maze task is likely attributed to dysfunction of the central cholinergic system due to disturbance of energy metabolism and hypoxia in the ischemic brain. Consistent with previous reports from this 3,11) and other laboratories, 26,27) we found that transient ischemia caused a significant reduction of the ACh level in the hippocampus and that pretreatment with a cholinesterase inhibitor tacrine produced a protective effect not only on learning deficits but also on the reduction of the hippocampal ACh level in T2VO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Choline is accumulated in all tissues via simple diffusion or specific carrier mechanisms (Zeisel et al 1980). Under normal physiological conditions, the brain concentration of choline varies within a range of 10 -20 M and can rise to over 100 M in a number of pathophysiological conditions attributed to abnormal phospholipid metabolism, such as neural trauma and chronic degenerative disorders, including Alzheimer's disease (Farooqui and Horrocks 1994;Jope and Gu 1991;Klein et al 1997;Scremin and Jenden 1991).…”
Section: Introductionmentioning
confidence: 99%